Development of cryptogames with Unity on an Ethereum Blockchain Test Network: Case Study and Challenges - Silva, Eduardo Jorge Lira Antunes da; Araújo, Cristina Souza de; Silva Junior, Jucimar Maia da; Gomes, Roberto Junio Rodrigues; Carvalho, Larissa Roque; Rodriguez, Luis Cuevas; Pinheiro, Clairon Lima (Journal on Interactive Systems, 2024)
The development of software aligned with Web3 innovations is essential to stimulate discussions on the application of these technologies in the scientific realm. This study presents the development of a ’cryptogame,’ a game that integrates blockchain technology to incorporate Non-Fungible Tokens (NFTs) into its functionalities. The paper explores fundamental Web3 concepts, with references to relevant literature, and details the development process, including the methodologies and models adopted. As a result, a puzzle game was created that utilizes NFTs as playable characters, allowing for the transfer of these assets between digital wallets. Furthermore, the study investigates the application of these concepts in adapting a traditional mobile game for the use of NFTs, demonstrating the necessary changes in user interface and game mechanics to support the integration with digital assets.